2008
DOI: 10.1097/npt.0b013e31818ee779
|View full text |Cite
|
Sign up to set email alerts
|

The Sony PlayStation II EyeToy: Low-Cost Virtual Reality for Use in Rehabilitation

Abstract: The objective of this study was to investigate the potential of using a low-cost video-capture virtual reality (VR) platform, the Sony PlayStation II EyeToy, for the rehabilitation of older adults with disabilities. This article presents three studies that were carried out to provide information about the EyeToy's potential for use in rehabilitation. The first study included the testing of healthy young adults (N = 34) and compared their experiences using the EyeToy with those using GestureTek's IREX VR system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(120 citation statements)
references
References 33 publications
2
114
0
4
Order By: Relevance
“…For example, the EyeToy has shown the potential to promote exercise [40] and enhance upper-limb-related motor functioning in patients with stroke [41]. However, it appears that the Wii has captured the imagination of those in rehabilitation settings as a means to facilitate rehabilitation.…”
Section: Rehabilitation With Activity- Promoting Gaming Systemsmentioning
confidence: 99%
“…For example, the EyeToy has shown the potential to promote exercise [40] and enhance upper-limb-related motor functioning in patients with stroke [41]. However, it appears that the Wii has captured the imagination of those in rehabilitation settings as a means to facilitate rehabilitation.…”
Section: Rehabilitation With Activity- Promoting Gaming Systemsmentioning
confidence: 99%
“…In virtual reality, people perform diverse tasks and accomplish predetermined goals using technological simulated scenes by reacting as if they are performing the actions in reality (Holm and Priglinger 2008). This method provides an interesting and fun therapy, increasing motivational effects (Rand et al 2008). Virtual reality provides visual, auditory and proprioceptive, and can also stimulate cognition (Schultheis and Rizzo 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Post stroke, hundreds to thousands of repetitions of specific task practice are required for motor relearning [12]; however, Lang and colleagues [13] found that individuals post stroke are not obtaining nearly enough upper extremity practice in typical therapy sessions, with an average of less than two active assisted or purposeful upper extremity movements per minute of therapy time. Gaming provides much more practice [4], in part because it is less boring and more engaging [14][15][16]. In a summary of systematic reviews of therapeutic exercise, Taylor and colleagues found that therapeutic exercise was more effective if it was relatively intense, targeted, and individualized [17].…”
Section: Background and Purposementioning
confidence: 99%